Bilateral vocal fold palsy due to ingested battery in the postcricoid area/proximal esophagus. Issue 7 (26th April 2021) - Goussard, Pierre; Morrison, Julie; Nel, Etienne; Mfingwana, Lunga; Andronikou, Savvas; Blokland, Rachel A.; Mukhtar, Abdiwahab; Loock, James W.; de Bruyn, G. H. M.
Abstract: Stridor is a common symptom associated with foreign body aspiration. In most cases, this is due to the foreign bodies lodging in the supraglottis, glottis, subglottis, or high extra‐thoracic trachea. Infrequently, foreign bodies located in the esophagus cause stridor. The ingestion of button batteries (BBs) has been reported to cause multiple problems. The incidence has been estimated at 10.5 per million people per year with a case fatality rate of 0.5%. BBs predominantly cause esophageal mucosal injury. Mechanisms of injury include pressure necrosis, electrolysis, caustic exposure, or heavy metal toxicity. The reported complications include severe esophageal ulceration, trachea‐esophageal fistula or aorto‐esophageal fistula, and pneumonia. Vocal fold pathology after battery ingestion, other than edema of cords, has been rarely reported. We describe a case of acute bilateral vocal fold dysfunction and review the literature.